Step by Step Design Analysis and Calculations of an African Breadfruit Dehulling Machine - S, Ozigbo Emmanuel; M, Murphy Kayode (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
African breadfruit seeds dehulling is a lucrative business in Nigeria. There is a high demand of the seeds in Southeastern of the Country. A little quantity of it is highly priced in the market. Despite the high demand of the breadfruit seeds for both nutritional and medicinal value, the rural processors usually dodge the production process. This is as a result of hard labour, time wasted and rigorous processes as associated with the manual method of dehulling the seeds which are usually over 900 seeds in a single fruit, spongy pulp. The seeds have two coats, the outer coat is usually harder and thicker than the inner coat which make dehulling operation more tedious. The dehulling takes about 70% operation of the African breadfruit processing. Therefore, this paper reviewed the types of materials that can be used for fabrication a dehuller; designs considerations; design analysis and calculations of an African breadfruit seeds dehuller so as to provide a working document for designers and fabricators who may want to go into the production of African breadfruit seeds dehullers.